Combination of infrared thermal imaging camera and ESP32 microcontroller - Nishonov Ilhomjon Umaralievich (Genius Journals, 2023)
This article presents a research analysis of the effect of the CuP2 element as a modifier on the wear resistance of the gray cast iron low – alloyed liquid cast iron alloy. Based on the obtained results, the increase in the number of crystallization centers of the cast alloy and the formation of a fine granular structure led to a significant increase in the wear resistance property of the cast product
Keywords: ESP32 microcontroller; mlx90640 Infrared Thermal Imaging Camera